Permanent Missions to the United Nations, No. 311 - United Nations (United Nations, 2023)
This book serves as a directory of the Permanent Missions to the United Nations in New York, as well as a listing of their diplomatic personnel. It also includes information on Observer Offices, Specialized Agencies, and other UN organs and bodies.